Oil Shale Development in the United States Prospects and Policy Issues - Bartis, James T. (RAND Corporation, 2005)
In the early 1980s, industry and government took a hard look at the economics of extracting oil from vast deposits of shale that lie beneath the western United States. Oil prices subsided, and interest waned. With oil prices spiking and global demand showing no signs of abating, reexamining the economics of oil shale makes sense. In this report, the authors describe oil shale resources; suitability, cost, and performance of new technologies; and key policy issues that need to be addressed by government decisionmakers in the near future.